New Frontiers for the Cytoskeletal Protein LASP1 - Butt, Elke; Raman, Dayanidhi (Frontiers in Oncology, 2018)
In the past two decades, LIM and SH3 protein 1 (LASP1) has developed from a simple actin-binding structural protein to a tumor biomarker and subsequently to a complex, nuclear transcriptional regulator. Starting with a brief historical retrospect, this review will mainly compare and contrast LASP1 and LASP2 from the angle of the newest data and importantly, examine their role in transcriptional regulation. We will summarize the current knowledge through pictorial models and tables including the roles of different microRNAs in the differential regulation of LASP1 levels and patient outcome rather than specify in detail all tumor entities. Finally, the novel functional roles of LASP1 in secretion of vesicles, expression of matrix metalloproteinases and transcriptional regulation as well as the activation of survival and proliferation pathways in different cancer types are described.